2006
DOI: 10.1126/science.1124872
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance High- T c Superconducting Wires

Abstract: We demonstrated short segments of a superconducting wire that meets or exceeds performance requirements for many large-scale applications of high-temperature superconducting materials, especially those requiring a high supercurrent and/or a high engineering critical current density in applied magnetic fields. The performance requirements for these varied applications were met in 3-micrometer-thick YBa2Cu3O(7-delta) films epitaxially grown via pulsed laser ablation on rolling assisted biaxially textured substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
255
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(279 citation statements)
references
References 15 publications
21
255
2
1
Order By: Relevance
“…Different substrates are used for different application, and lattice match to give epitaxy and chemical compatibility are among the important considerations. Special attention has also been directed towards the preparation of superconducting wires, typically consisting of a metallic tape with a superconducting coating, which can enable large-scale applications for electric-power and magnetic applications (Larbalestier et al 2001;Rupich et al 2004;Kang et al 2006). Here, a buffer layer between the metal substrate and the superconducting layer is needed to protect the metal substrate from oxidation and to give epitaxial growth of the superconducting film (Obradors et al 2004).…”
Section: Superconducting Thin Filmsmentioning
confidence: 99%
“…Different substrates are used for different application, and lattice match to give epitaxy and chemical compatibility are among the important considerations. Special attention has also been directed towards the preparation of superconducting wires, typically consisting of a metallic tape with a superconducting coating, which can enable large-scale applications for electric-power and magnetic applications (Larbalestier et al 2001;Rupich et al 2004;Kang et al 2006). Here, a buffer layer between the metal substrate and the superconducting layer is needed to protect the metal substrate from oxidation and to give epitaxial growth of the superconducting film (Obradors et al 2004).…”
Section: Superconducting Thin Filmsmentioning
confidence: 99%
“…After the seminal works demonstrated that second-phase additions 4,12 to RE-Ba-Cu-O (rare earth (RE)) (REBCO) thin films grown using pulsed laser deposition (PLD) significantly improved the current carrying performance in an applied magnetic field, 3,[13][14][15] it was shown that the morphology of the inclusions depends on the synthesis 1 Materials Physics and Applications Division, Los Alamos National Laboratory, Los Alamos, NM, USA; 2 Graduate School of Science and Technology, Seikei University, Tokyo, Japan; 3 Nanostructures Research Laboratory, Japan Fine Ceramics Center, Nagoya, Japan; 4 National Institute of Advanced Industrial Science and Technology, Ibaraki, Japan; method (that is, in situ vs ex situ). 3,16 Moreover, recent work has shown that large quantities (⊞10%) of second-phase additions are required to obtain the desired level of performance in superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The pinning centres, in order to be effective, need to be nanoparticles, less than 15 vol% of the superconductor, and be randomly distributed to provide isotropic 3D pinning. [5][6][7][8][9][10][11][12] in pulsed laser ablated (PLD) YBCO films have been recently investigated for creating nanoparticles for flux pinning. The pinning effect of each of these materials and processes provides effective pinning at various magnetic field levels.…”
Section: Introductionmentioning
confidence: 99%